Urdu version of Sesame Street from April - Mohiuddin, Saeed (The News International, 2009)
Pakistani children would be able to watch the Urdu version of Sesame Street – the most-watched children’s television show in the world – five days a week on both PTV 1 and PTV 2...
KerkoCite.ItemAlsoKnownAs: 2405685:JFFPPRY2